Comparison of radiographic changes in the alveolar crest after extraction of fully and partially erupted premolars during orthodontic treatment: A retrospective analytical study - Sanam Darban Hosseini; Mojgan Kachoei; Masoumeh Faramarzi; Mahdiyeh Esmaeilzadeh (Tabriz University of Medical Sciences, 2021)
Background. The alveolar process plays an essential role in providing dental support and gradually disappears with tooth loss. Space deficiency can cause one premolar to remain semi-erupted adjacent to a fully-erupted premolar. During orthodontic treatment, each of these premolars can be extracted. This retrospective study aimed to compare radiographic changes of the alveolar crest due to orthodontic movements of fully-erupted and semi-erupted premolars into the extraction sites before and after treatment. Methods. The patients were divided into the fully-erupted premolar extraction (first) group and the semi-erupted premolar extraction (second) group. The distance between the cementoenamel junction (CEJ) and the alveolar crest, from the distal aspect of the canine to the mesial aspect of the first molar, was measured on panoramic radiographs of 78 patients (39 from each group) before and after treatment with a digital caliper. Changes in the alveolar crest were compared between the two groups. Finally, the height differences of the alveolar crest in mesial and distal aspects of the remaining premolars in both groups were calculated at the end of treatment. Descriptive statistical analyses and paired and independent t tests were used in the study. Results. The distance from the CEJ to the alveolar crest at mesial and distal aspects in the first group and the distal aspect of the extraction site in the second group increased significantly. However, changes at the mesial aspect were not significant in the second group. Comparing the alveolar crest height between the two groups and between the mesial and distal aspects of the remaining premolar tooth indicated no significant differences. Conclusion. No significant difference was observed between the extraction of a fully-erupted or semi-erupted premolar to obtain greater alveolar height.